IMPROVING THE STUDENTS’ ENGLISH PRONUNCIATION THROUGH THE BABBEL PLATFORM - Ahmad Rizky Ardi Pratama; Didik Santoso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the effectiveness of the Babbel platform in enhancing English pronunciation skills among senior high school students. Many students struggle with clear and accurate pronunciation, which affects their communication confidence and fluency. The study aims to evaluate the effectiveness of the Babbel platform in improving English pronunciation skills among senior high school students. A total of 25 students, selected through purposive sampling based on predetermined criteria, participated in this cyclical action research. These students, with beginner- to-intermediate English proficiency, used Babbel’s pronunciation practice feature for 30-minute sessions. The research was conducted over one cycle, involving four phases: planning, implementing, observing, and reflecting. In the planning phase, activities were designed based on Babbel’s features to target students' specific pronunciation difficulties. The implementing phase involved practicing pronunciation with real-time feedback from the app. During the observing phase, pre- and post-tests were administered, showing a 61.6% improvement in pronunciation, with the mean score rising from 45.00 to 86.60. Semi-structured interviews provided qualitative insights into students' learning experiences. In the reflecting phase, both quantitative and qualitative data were analyzed to assess improvements in pronunciation. In the planning phase, activities were designed based on Babbel’s features to target students' specific pronunciation difficulties. The implementing phase involved practicing pronunciation with real-time feedback from the app. During the observing phase, pre- and post-tests were administered, showing a 61.6% improvement in pronunciation, with the mean score rising from 45.00 to 86.60. Semi-structured interviews provided qualitative insights into students' learning experiences. In the reflecting phase, both quantitative and qualitative data were analyzed to assess improvements in pronunciation. Results confirmed a significant enhancement in pronunciation skills and increased student confidence. Data validity was ensured through triangulation, incorporating pre- and post-test results, interviews, and observations. The findings suggest that the Babbel platform effectively improves English pronunciation and boosts learners' confidence, contributing to more effective communication.